The Influence of Tax Knowledge, Modernization of Tax Administration, and Islamic Value on Tax Compliance of MSMEs in Yogyakarta - Ryanica Nabila, Tiffanny; Fitri Rahajeng, Dinik (Journal of Islamic Contemporary Accounting and Business, 2023)
The increase in the number of MSMEs in line with the increasing number of taxpayers in Indonesia provides the potential for tax revenue. In fact the contribution to taxes is still very low. Therefore, this study intends to determine the effect of tax knowledge, modernization of tax administration and Islamic value on MSME tax compliance. The sample in this study, namely SMEs in the Province of the Special Region of Yogyakarta, was selected using a random sampling technique. The research method is multiple regression analysis method. 210 respondents who have been processed produce that tax knowledge and modernization of tax administration have a positive and significant effect on MSME taxpayer compliance. For further research, it is expected to add other variables related to tax compliance so that it can provide a broader picture.